Performance de l'action publique et carrières de jeunes délinquants - Chéronnet, Hélène (2015)
O artigo analisa o recente desenvolvimento do sistema de justiça juvenil na França, abordando a redefinição do tratamento institucional da delinquência juvenil, por meio da evolução de dispositivos penais, como a criação de centros educativos reforçados e de centros de internação. Propõe, com base em uma análise empírica, uma tipologia que busca desconstruir uma representação globalizante, veiculada nos discursos públicos de um jovem delinquente multireincidente que elege condutas delinquentes como modo de vida. The article Performance of Public Action and Criminal Youth Careers examines the recent evoluÂtions of juvenile in France. It considers the redefining of the institutional treatment of juvenile deliquency through the evolution of the appliance of penal placÂing and more particularly the creation of reinforced educational centres and closed educational centres. It proposes, on the basis of an empirical analysis, a typology which enables to deconstruct a globalizing representation, conveyed by public discourse, of a multi recidivist young offender who sets up delinÂquent behaviours as a way of life.Keywords: juvenile justice, education under constraint, withdrawal from delinquency, performance of public action, logics of action